The Role of Social Media in Developing an Online Learning Community for Islamic Religious Education - Prasetyo, Fabian Eka; Roswanda Nuraini; Naza Sefti Prianita; H. Amali (PT FORMOSA CENDEKIA GLOBAL, 2024)
Social media has become a crucial platform for supporting and developing online learning communities for Islamic education. This platform provides easy access for individuals and groups to share knowledge, experiences, and perspectives related to Islam globally. In online learning communities, social media acts as a bridge connecting students with educators, scholars, and fellow learners from various backgrounds and geographic regions. Interactive features such as discussion forums, study groups, and Q&A sessions enable active and collaborative participation in the learning process. Additionally, social media provides a space for sharing educational content such as articles, videos, and podcasts that enrich the understanding of Islamic region. However, it is important to maintain the quality of content and ensure the accuracy of the information shared. By utilizing social media wisely, online learning communities for Islamic education can grow and contribute positively to the enhancement of religious understanding and practices in the digital age